2021
DOI: 10.1177/2050312120986733
|View full text |Cite
|
Sign up to set email alerts
|

Clinical complications in patients with primary and recurrent Clostridioides difficile infection: A real-world data analysis

Abstract: Objective: Clostridioides difficile infection and recurrent C. difficile infection result in substantial economic burden and healthcare resource use. Sepsis and bowel surgery are known to be serious complications of C. difficile infection. This study evaluated clinical complications in patients with C. difficile infection and recurrent C. difficile infection during a 12-month period following the primary C. difficile infection. Methods: A retrospective analysis of commercial claims data from the IQVIA PharMetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 32 publications
2
38
0
Order By: Relevance
“… 18 A single-center study of patients with rCDI found a 22% BSI rate after CDI treatment with antibiotics. 20 In a claims study among a younger population (mean age 48 years) with CDI, sepsis occurred in 16.5%, 27.3%, 33.1%, and 43.3% of patients after 0, 1, 2, and 3+ rCDI episodes, respectively, during the 12-month follow-up, 19 supporting our finding of increased incidence among those with rCDI. The mean time to CDI recurrence in that study was approximately 30 days, similar to our study (range 31.6–35.0 days).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“… 18 A single-center study of patients with rCDI found a 22% BSI rate after CDI treatment with antibiotics. 20 In a claims study among a younger population (mean age 48 years) with CDI, sepsis occurred in 16.5%, 27.3%, 33.1%, and 43.3% of patients after 0, 1, 2, and 3+ rCDI episodes, respectively, during the 12-month follow-up, 19 supporting our finding of increased incidence among those with rCDI. The mean time to CDI recurrence in that study was approximately 30 days, similar to our study (range 31.6–35.0 days).…”
Section: Discussionsupporting
confidence: 80%
“… 17 Previous studies report that sepsis occurs in 16–43% of patients with CDI, with higher frequency after rCDI and for older patients. 18 – 21 This rate is much higher than the 6.0% incidence of sepsis for all hospitalized patients aged ⩾20 years in the United States. 22 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If conditions are favorable, e.g., after antibiotic-induced dysbiosis when the reduced microbiome fails to convert primary bile acids into secondary bile acids, C. difficile spores are able to germinate to successively colonize the large intestine ( Theriot et al, 2014 ; Pike and Theriot, 2020 ). Even though antibiosis mostly stops the acute infection, C. difficile spores as well as some vegetative cells survive in the intestine and can subsequently cause a relapse as soon as antibiotic concentrations are sufficiently low ( Goulding et al, 2009 ; Chilton et al, 2018 ; Castro-Córdova et al, 2020 ; Feuerstadt et al, 2021 ; Normington et al, 2021 ). Initially, sporulation was assumed to be one of the major prerequisites for C. difficile’s persistence under clinical circumstances.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with CDI often present with watery diarrhea and abdominal pain, but symptoms can also include fever, hypotension, or ileus in more severe cases (5); complications can include sepsis or colectomy/ileostomy (6)(7)(8)(9)(10)(11). Testing for CDI is recommended for patients who have unexplained, new onset diarrhea (at least 3 unformed stools over ≥24 h) using a nucleic acid amplification test alone or as part of an algorithm that includes glutamate dehydrogenase or stool toxin test (12).…”
Section: Introductionmentioning
confidence: 99%